2005
DOI: 10.5713/ajas.2005.1294
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Growth Performance and Meat Quality Parameters by Restricted Diet during Finishing Days

Abstract: The objective of the present study was to investigate the effects on growth performance, meat quality parameters and fatty acids of meat by restricted diet amount on finishing Berkshires. A total of 180 pigs (Berkshire, initially 52 kg BW) at 100 days of age were allotted in arrangement in a completely randomized design (10 pigs per pen), blocked arrangement of treatments with 3 replications. The variables were market ages (180, 200 and 220 days) and in which was also included sex (gilts and barrow). All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Similarly, previous studies also reported that shear force, cooking loss and pH are not affected by sex (Cisneros et al, 1996;Weatherup et al, 1998;Hamilton et al, 2000). In addition, Lee et al (2005) reported color and pH of longissimus dorsi muscle were not affected by the sex. While loin eye area is higher in gilts compared with barrows (p<0.05), which similarly agrees with Leach et al (1996) and Unruh et al (1996).…”
Section: Meat Characteristicssupporting
confidence: 68%
“…Similarly, previous studies also reported that shear force, cooking loss and pH are not affected by sex (Cisneros et al, 1996;Weatherup et al, 1998;Hamilton et al, 2000). In addition, Lee et al (2005) reported color and pH of longissimus dorsi muscle were not affected by the sex. While loin eye area is higher in gilts compared with barrows (p<0.05), which similarly agrees with Leach et al (1996) and Unruh et al (1996).…”
Section: Meat Characteristicssupporting
confidence: 68%
“…The lipid content was low in even 1‐year‐old deer (2.0% FM) and female deer (2.1% FM) reared for a short period, like those in beef (1.19–3.62% FM) (Bureš & Bartoň ) and pork (2.28–3.76% FM) (Lee et al . ). According to Wiklund et al .…”
Section: Resultsmentioning
confidence: 97%
“…Higher levels of body fat and the fat content of meat in older males than in younger males in pigs (Berkshire) and beef cattle (Simmental × Charolais) have been reported (Lee et al . ; Bartoň et al . ; Bureš & Bartoň ), showing a different pattern from that of the age difference in our Yeso sika deer.…”
Section: Resultsmentioning
confidence: 99%
“…This combination of low muscle pH and high muscle temperature can affect the ultimate meat quality by causing excessive denaturation of the muscle protein (Offer, 1991;Choi et al, 2006). Also, the muscle pH, temperature (Homer and Matthews, 1998), and final pork quality can vary between processing plants ( Van der Wal et al, 1999;Hambrecht et al, 2003;Lee et al, 2005;Gardner et al, 2006;Park et al, 2007).…”
Section: Introductionmentioning
confidence: 99%